PERSEPSI WANITA USIA SUBUR (WUS) TENTANG KANKER LEHER RAHIMÂ DI DUSUN MEJERO DESA JUMENENG KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Sudarsih, Sri; Peni, Tri (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The amount of cases of cervical cancer in Indonesia is still quite high. This cancer is a type of cancer that affects most women in Indonesia. Every day new cases estimated to emerge 40-45 and 20-25 women die each day from cervical cancer. The purpose of this study was to determine the perception of women of childbearing age about cervical cancer in RT 4 Mejero hamlet village Jumeneng Mojoanyar District of Mojokerto regency. This research is descriptive. The population in this study were all women childbearing in Village Mejero Jumeneng Mojoanyar District of Mojokerto as many as 30 women childbearing. The sampling technique used is non-probability sampling (total sampling). The variable in this study is the perception of women of childbearing age about cervical cancer. The instrument used in this study was a questionnaire. The results showed that most respondents have a positive perception is as much as 66.67%. A persons perception is influenced by several factors, one of which is a factor of individual characteristics, namely education, the higher ones education it will be easier to receive information. Health workers are expected to improve services through health education so as to improve the perception of women of childbearing age are negative to cervical cancer.Keywords:Perception, women of childbearing age, cervical cancer